KEBIJAKAN JEPANG DALAM MERESPON ANCAMAN MISIL KOREA UTARA PADA TAHUN 2012-2017 - Anggal Detry Natalia Sitohang; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research explains about Japan and North Korea have unstable relation caused by history aspect. This thing was caused every country try to strengthen their security. Japan increased and kept its security with using Missile Air Defense. The enhancement analogously with increasing of device and fund of Japan military. This research will examine Japan Policy in Facing the Threat of North Korea Missile in 2012-2017.The method that used in this research is qualitative method with data source from library research. The theory is defensive neo-realism by Kenneth Waltz, that is for focusing how anarchy world can influence countries to increase the capability of their country. The concept is security dilemma by John Herz.This research shows that North Korea had done nuclear experiment that had crossed over the sea of Japan. This experiment had been done at the number of five times and the last one at 2017. This is the reason of Japan to increase the Missile Air Defense, that is to have strong security on threating from North Korea. So, Japan can achieve prosperity and do activities normally as a country. Keywords: Missile Air Defense, Threat , Defensive Neo-realism, Security Dilemma.